Assessment of the mechanical behaviour of glass fibre composites with a tough polydicyclopentadiene (PDCPD) matrix. (November 2015) - Vallons, Katleen A.M.; Drozdzak, Renata; Charret, Mathieu; Lomov, Stepan V.; Verpoest, Ignaas
Abstract: The use of a tough thermoset polydicyclopentadiene (PDCPD) as a matrix material for composites was explored. A PDCPD–glass fibre composite and an equivalent epoxy composite were compared. Fibre–matrix adhesion quality was assessed by transverse bending tests. The materials were subjected to compression tests, impact tests, static tensile tests and tensile fatigue tests. The results indicate that the tough behaviour of the PDCPD matrix markedly influences the composite damage resistance. The size of the impact damage in the PDCPD composite was half of that in the epoxy composite. The tensile tests indicated no significant difference in tensile strength, but the damage before failure was found to be much more severe in the epoxy samples. The fatigue results showed a much lower variation in fatigue life for the PDCPD material than for the epoxy material, as well as clear differences in damage development for the two materials.